2022
DOI: 10.21203/rs.3.rs-688105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of NCAPG in ovarian cancer is associated with ovarian cancer proliferation and apoptosis via p38 MAPK signaling pathway

Abstract: Background Non-SMC condensin I complex subunit G (NCAPG), a member of the subunit of condensin complex, is significantly overexpressed in various cancers and involved in the pathogenesis of cancers. However, the roles of NCAPG in ovarian cancer remain unclear. Methods The mRNA expression, overall survival and disease-free survival of NCAPG in ovarian cancer was analysed by GEPIA and KM plotter database, the expression levels of NCAPG in OC tissues and cell lines were determined by qPCR and immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…NCAPG (non-SMC condensin I complex, subunit G) is a mitose-associated chromosome condensation protein (32). Related studies have shown that NCAPG is signi cantly overexpressed in various tumors, including colorectal cancer, hepatocellular carcinoma, lung cancer, etc., and affects the biological functions of tumor cells such as proliferation, migration, invasion and apoptosis (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…NCAPG (non-SMC condensin I complex, subunit G) is a mitose-associated chromosome condensation protein (32). Related studies have shown that NCAPG is signi cantly overexpressed in various tumors, including colorectal cancer, hepatocellular carcinoma, lung cancer, etc., and affects the biological functions of tumor cells such as proliferation, migration, invasion and apoptosis (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, microRNA (miR)-566 directly targets PSKH1, regulating colon cancer cell proliferation, migration and invasion (12). Various factors contribute to the development of tumors via the p38/MAPK signaling pathway (13,14). For example, downregulation of Non-SMC condensin I complex subunit G (NCAPG) could suppress OC cell proliferation and invasion via activating the p38 MAPK signaling pathway (13).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors contribute to the development of tumors via the p38/MAPK signaling pathway (13,14). For example, downregulation of Non-SMC condensin I complex subunit G (NCAPG) could suppress OC cell proliferation and invasion via activating the p38 MAPK signaling pathway (13). The p38 pathway serves a crucial role in facilitating muscle differentiation, which confers its anti-tumor properties (15).…”
Section: Introductionmentioning
confidence: 99%